2020
DOI: 10.1002/ece3.6842
|View full text |Cite
|
Sign up to set email alerts
|

There’s a storm a‐coming: Ecological resilience and resistance to extreme weather events

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 52 publications
0
26
0
1
Order By: Relevance
“…Undoubtedly, climatic change has the potential to substantially alter persistence of taxa around the globe, and has been identified as a key stressor for birds (Bateman et al, 2016), plants (Scholze et al, 2006), herpetofauna (Araújo et al, 2006), arthropods (Halsch et al, 2021), and mammals (Schloss et al, 2012), causing significant changes in species phenology, abundance, and distribution (Lenoir et al, 2016;Neilson et al, 2020). Although climate impacts are of mounting concern (Maxwell et al, 2016), climate change is only one of many anthropogenic stressors contributing to biodiversity declines (Morris et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, climatic change has the potential to substantially alter persistence of taxa around the globe, and has been identified as a key stressor for birds (Bateman et al, 2016), plants (Scholze et al, 2006), herpetofauna (Araújo et al, 2006), arthropods (Halsch et al, 2021), and mammals (Schloss et al, 2012), causing significant changes in species phenology, abundance, and distribution (Lenoir et al, 2016;Neilson et al, 2020). Although climate impacts are of mounting concern (Maxwell et al, 2016), climate change is only one of many anthropogenic stressors contributing to biodiversity declines (Morris et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of these stressors on coastal lagoons and estuaries can be more destructive when there is a combination of two or more due to the cumulative impacts. In particular, these stresses can coincide with the impacts of hurricanes and extreme climatic events, which are expected to increase their frequency, intensity and stochasticity as a result of climate change (Bender et al 2010;Knutson et al 2015;Hampel et al 2019;Neilson et al 2020).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…We do not think that this is due to exceptionally beneficial post‐drought years for the species, at least not weather‐wise (the average precipitation suggested that 2019 and 2020 were rather ‘normal’ years, Figure S3), but we can expect higher population growth rates due to a decreased competition (i.e. negative density dependence – Zimmermann, Blazkova, et al, 2011; Neilson et al, 2020). However, the most important reason for the fast recovery of our metapopulation is most likely that the patch network is relatively large and well connected.…”
Section: Discussionmentioning
confidence: 98%
“…These events may have large effects on many ecosystems and species (e.g. Maxwell et al, 2019; Neilson et al, 2020; Parmesan et al, 2000). Increasing magnitude and frequency of extreme weather events can have even larger impact on population persistence than increases in, for example, average temperatures (Bauerfeind & Fischer, 2014; Parmesan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%